The Implementation of Moral Character Education in SD Tunas Metropolitan - Darmawan Sunarja; Encep Syarif Nurdin; Ace Suryadi; Edi Suresman (Jurnal Elementaria Edukasia, 2024)
This research aims to determine the implementation of character education in elementary schools in SD Tunas Metropolitan. Character education has recently become the subject of public debate regarding its implementation and the loss of character values such as honesty, courtesy, friendliness and religiosity which is gradually becoming an erosion of foreign culture. Hopefully this research can be a reference in building and implementing character education in elementary schools and the community. The type of research used was qualitative research conducted at SD Tunas Metropolitan. Primary data was collected from the results of in-depth interviews with key informants, namely: the principal, deputy principal, principal and students. After the data is collected, it is then analyzed using inductive techniques with the following steps: data reduction, data presentation, and data verification. The results of this research are that student character formation can be done through internal strategies and external strategies. Internal strategies can be implemented through four activities, namely activities in the teaching and learning process, daily activities in the form of school culture, habit formation activities, and internal and external activities. Meanwhile, external strategies can be implemented through the family environment and community environment. If all these strategies can be implemented well, the student's personality will be formed firmly.